MYSAP Inland baseline survey - Nway, Hsu Myat (WorldFish, 2023)
The dataset for the baseline study conducted by Mekong Economics for the project INLAND MYSAP titled ‘Improving the production, nutrition, and market values of small-scale aquaculture in Myanmar’s Shan State, Mandalay Region, and Sagaing Region’. The survey was executed in order to understand the current levels of aquaculture production of project beneficiaries, the level of access to important aquaculture inputs, and the population’s dietary diversity.